HIV-Associated Interactions Between Oral Microbiota and Mucosal Immune Cells: Knowledge Gaps and Future Directions - Coker, Modupe O.; Cairo, Cristiana; Garzino-Demo, Alfredo (Frontiers in Immunology, 2021)
Even with sustained use of antiretroviral therapy (ART), HIV-infected individuals have an increased risk of systemic comorbid conditions and oral pathologies, including opportunistic infections, oral mucosal inflammation, and gingival and periodontal diseases. The immune-mediated mechanisms that drive this increased risk, in the context of sustained viral suppression, are unclear. HIV infection, even when controlled, alters microbial communities contributing to a chronic low-grade inflammatory state that underlies these non-HIV co-morbidities. The higher prevalence of dental caries, and mucosal and periodontal inflammation reported in HIV-infected individuals on ART is often associated with differentially abundant oral microbial communities, possibly leading to a heightened susceptibility to inflammation. This mini-review highlights current gaps in knowledge regarding the microbe-mediated oral mucosal immunity with HIV infection while discussing opportunities for future research investigations and implementation of novel approaches to elucidate these gaps. Interventions targeting both inflammation and microbial diversity are needed to mitigate oral inflammation-related comorbidities, particularly in HIV-infected individuals. More broadly, additional research is needed to bolster general models of microbiome-mediated chronic immune activation and aid the development of precise microbiota-targeted interventions to reverse or mitigate adverse outcomes.